HUBUNGAN DURASI TIDUR DAN POLA ASUH TERHADAP TUMBUH KEMBANG ANAK USIA 4-5 TAHUN - lilik ariyanti (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Continuous growth and development, several influencing factors are sleep duration and parenting patterns.The purpose of this research is to ascertain whether parenting styles and sleep duration have an impact on the growth and development of children between the ages of four and five. Cross-sectional study design was used. The Denver Development Screening Test sheet, the Pittsburgh Sleep Quality Index (PSQI), and the Parenting Styles and Dimensions Questionnaire (PSDQ) were the measurement tools utilized. There were twenty-one children in the sample, ages four to five. Purposive sampling is used in the sampling procedure. Statistical test results of sleep duration with growth (p value: 0.323), sleep duration with development (p value: 0.696), parenting patterns with growth (p value: 0.247) and parenting patterns with development (p value: 0.497). Conclusion: There is no relationship between sleep duration and parenting patterns on the growth and development of children aged 4-5 years